Ankunft der Besatzung des Lloyd-Schiffes "Bremen" in Berlin. Ahrens in der Mitte. Serie von 2 Fotos
Ankunft der Besatzung des Lloyd-Schiffes "Bremen" in Berlin. Ahrens in der Mitte. Serie von 2 Fotos.